Body and subjectivation: elements for the analysis of school conflicts - Yuing Alfaro, Tuillang; Godoy Peña, Lorena (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This text explores different ways in which conflicts can be regarded in educational scenarios, considering the Chilean mobilization of 2006 as an example. For this purpose it takes advantage of the contributions made by Foucault on power and institutions: at school, the body of the student has become subject of appropriations and tensions. Through regulations and evasions, an identity dispute between the school and the youth, that seeks to become subjectivities by taking on discourse in a critical manner, are manifested. Thus, the text questions what has been the role of these identity and subjectivity processes in the breeding of student demonstrations. What opportunities to develop pedagogical practices that answer to the different scenarios in the current political and academic panorama are presented by these strifes? Finally, it interprets the concept of experience and childhood from the point of view of Giorgio Agamben, in order to test some hypotheses surrounding these questions.